KOMPARATIF INTONASI KARAKTER NOBITA DALAM FILM STAND BY ME DORAEMON PADA SULIH SUARA JEPANG DAN INDONESIA - Nasywa Rihhadatul Aisy; Rumentha Margareth Manurung (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research examines the comparative intonation of the character Nobita in the film “Stand By Me Doraemon” between the original Japanese dubbing and the Indonesian dubbing. Using the high-down intonation framework by Ladd (2008), this study aims to evaluate how the Indonesian dubbing reconstructs emotional quality and pragmatic functions within illocutionary speech acts, as conceptualized by Searle (1969). The study employs a sequential explanatory mixed-methods approach, utilizing Praat software for acoustic-phonetic analysis to extract fundamental frequency () and duration parameters from twelve dialogue segments. The findings indicate that despite significant variations in frequency and duration, often due to linguistic structural differences, the Indonesian voice actor successfully maintains the character's pragmatic intent through adaptive prosodic manipulation, such as ascending pitch contours, precise articulatory markers, and rhythmic breathing patterns. This research concludes that the Indonesian dubbing effectively reproduces the emotional and pragmatic nuances of the original characterization, ensuring the consistency of Nobita’s emotional expression in the target language.